2011
DOI: 10.1038/onc.2011.181
|View full text |Cite
|
Sign up to set email alerts
|

Twist2 contributes to breast cancer progression by promoting an epithelial–mesenchymal transition and cancer stem-like cell self-renewal

Abstract: The epithelial to mesenchymal transition (EMT) is a highly conserved cellular programme that has an important role in normal embryogenesis and in cancer invasion and metastasis. We report here that Twist2, a tissue-specific basic helix-loop-helix transcription factor, is overexpressed in human breast cancers and lymph node metastases. In mammary epithelial cells and breast cancer cells, ectopic overexpression of Twist2 results in morphological transformation, downregulation of epithelial markers and upregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 59 publications
(66 reference statements)
9
130
5
Order By: Relevance
“…We tested this idea by growing multicellular structures from Michigan Cancer Foundation-7 (MCF-7) cells and then quantifying the extent of line formation and disorganization. The MCF-7 cell line was originally derived from a patient with invasive ductal carcinoma, represents an advanced stage of tumor progression (37,38), and has further compromised integrity of cell-cell adhesion (39,40). When grown, extracted, and deposited on collagen 1 like the MCF10AT acini, the MCF-7 spheroids more readily spread, as expected.…”
Section: Significancementioning
confidence: 68%
“…We tested this idea by growing multicellular structures from Michigan Cancer Foundation-7 (MCF-7) cells and then quantifying the extent of line formation and disorganization. The MCF-7 cell line was originally derived from a patient with invasive ductal carcinoma, represents an advanced stage of tumor progression (37,38), and has further compromised integrity of cell-cell adhesion (39,40). When grown, extracted, and deposited on collagen 1 like the MCF10AT acini, the MCF-7 spheroids more readily spread, as expected.…”
Section: Significancementioning
confidence: 68%
“…3e23h). Consistent regulation of the EMTrelated genes (such as SNAIL, MTA3, AKT1 and LOXL2) [16][17][18][19][20][21] by NEDD9 was validated in both lung cancer cell lines with either NEDD9 overexpression or NEDD9 knockdown (Supporting Information Figs. 6a-6d).…”
Section: Nedd9 Promotes Partial Emt Process Of Lung Cancer Cellsmentioning
confidence: 81%
“…5b). It has been shown that E-cadherin expression in breast cancer cells is regulated at the level of mRNA transcription by transcription factors important for EMT such as ZEB1, Twist, Snail, and Slug [13][14][15] or by epigenetic mechanisms [16,17]; however, E-cadherin mRNA levels were not altered by E+ R5020 treatment in T47D cells (Fig. 5c).…”
Section: E+ps Treatment Decreases E-cadherin Protein In Breast Cancermentioning
confidence: 92%
“…The decrease or loss of E-cadherin protein is associated with poor prognosis in breast cancer patients [12]. Numerous studies have reported that E-cadherin mRNA expression is negatively regulated by transcription factors important for epithelial-to-mesenchymal transition (EMT) [13][14][15]. Based on in vitro studies, it has been proposed that cells composing ductal carcinoma in situ undergo EMT that is accompanied with decreased E-cadherin expression and become invasive.…”
Section: Introductionmentioning
confidence: 99%